A study of restructuring and its impact on the occupation-specific dispensation (OSD) positions at the Department of Agriculture, Land Reform and Rural Development, Western Cape, South Africa - Kotelo, Bulelwa (Stellenbosch : Stellenbosch University, 2024)
(Thesis (MPA)--Stellenbosch University, 2024.